Tests of the Black-Scholes and Cox Call Option Valuation Models: Discussion - Manaster, Steven (Journal of Finance, 1980)
Steven Manaster, Tests of the Black-Scholes and Cox Call Option Valuation Models: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 301-303